MODERASI DANIEL: TAFSIR HISTORIS-KRITIS MELLUI KACAMATA MODERASI BERAGAMA TERHADAP KITAB DANIEL 6:1-12 - Melinda Timbayo; Dirga Sinta Hayu; Raimawan (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines Daniel 6:1-12 through a historical-critical approach with a focus on religious moderation in the Christian context. The story of Daniel illustrates the steadfast faith of a minority figure facing political pressure in the Medo-Persian empire, while maintaining personal and professional integrity without compromising religious principles. This qualitative library research uses the biblical text as the primary data and theological literature and studies on religious moderation as secondary data. Historical-critical analysis explores the historical context, narrative structure, and sociopolitical dynamics, while thematic analysis highlights Daniel’s values of moderation, moral courage, and integrity. The study finds that Daniel’s moderation integrates spiritual discipline, moral courage, and professional competence, enabling Christian minorities to contribute positively in public spaces without losing religious identity. This narrative is relevant for contemporary religious moderation, emphasizing a balance between faithfulness to God, moral ethics, and social responsibility.